Managing virtual teams - DuFrene, Deborah Daniel 1954-; Lehman, Carol M. (Corporate communication collection, 2012)
Virtual teams are an integral part of today's global business environment. Traditional face-to- face communication is frequently replaced with technology-mediated communication methods including phone, e-mail, fax, synchronous chat programs, and videoconferencing. While virtual teams offer various advantages to organizations and individuals in flexibility and the ability to overcome geographic distance, they face unique challenges. Virtual teams are often made up of members of various cultures and ages with diverse communication styles. Men and women also tend to behave differently in virtual environments. Challenges occur in the forming, storming, norming, and performing phases of team development, and virtual teams must be able to cope effectively with those obstacles if they are to be successful and reach their potential. Team participants should be selected carefully for various personal characteristics that help ensure success and be trained in how to be effective virtual team members. Various team strategies can be implemented to improve effectiveness and satisfaction of virtual team members.